TREATMENT OUTCOMES AND FACTORS ASSOCIATED WITH POOR ADHERENCE AMONG CHILDREN RECEIVING ANTI-TUBERCULOSIS THERAPY (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Non-adherence to anti-tuberculous treatment can extend the duration of illness, contribute to loss to follow-up and reduce treatment success in children, but determinants of adherence in children are not fully understood.Methods: A prospective observational study of 184 children with drug-susceptible TB (DSTB) who were receiving treatment in a tertiary care center was conducted and adherence, treatment outcomes, and modifiable risk factors were assessed.Results: At least 90% of prescribed doses without a prolonged gap in treatment was documented in 141 (76.6%) children and in 43 (23.4%) children, poor adherence was documented, with overall treatment success of 88.0%, but lower among poorly adherent children, compared to those with good adherence (69.8% vs 93.6%, p